You and drugs - Abeleda, Alberto Jr. (Paranaque City, Philippines : GAMBAC Anti-Drug Publcations, Inc., 2005)
Our government and society are alarmed and worried about the growing menace of drug abuse.
CHAPTER 1. Drugs and Drug Abuse: Basic Facts and ideas -- 2. Drugs of abuse: What they are and what they do -- 3. Drug Abuse: Its impact on society -- 4. Saying "no" to drugs.
Includes bibliographical references.
Keywords: DRUG ABUSE